The Role of MiR-5094 as a Proliferation Suppressor during Cellular Radiation Response via Downregulating STAT5b - Ding, Nan (J Cancer, 2020)
MicroRNAs (miRNAs) play important roles in the regulation of cellular stress responses. We previously uncovered 10 novel human miRNAs which are induced by X-ray irradiation in HeLa cells using Solexa deep sequencing. The most highly expressed new miRNA, miR-5094, was predicted to target STAT5b. This study wonders whether miR-5094 participates in cellular radiation response via STAT5b. Firstly, direct interaction between miRNA-5094 and the STAT5b 3'-UTR was confirmed by luciferase reporter assay. Then, the radiation responsive expression of miR-5094 and STAT5b were measured in HeLa and Jurkat cells, and the expressions of down-stream genes of STAT5b after ionizing radiation (IR) were detected in HeLa cells. At last, the effects of miR-5094 on survival fraction, cell proliferation, cell cycle arrest and apoptosis induced by IR were investigated in HeLa cells, Jurkat cells and human peripheral blood T cells. It was found that up-regulation of miR-5094 by radiation induction or miRNA mimic transfection suppressed expression of STAT5b, and consequently decreased the transcription of down-stream Igf-1 and Bcl-2. Additionally, over expression of miR-5094 resulted in proliferation suppression and knockdown of miR-5094 by miRNA inhibitor after irradiation partially reversed the proliferation suppression induced by miR-5094 in HeLa cells, Jurkat cells and CD4(+) T cells. Collectively, our findings demonstrate that up-regulation of miR-5094 down-regulated the expression of STAT5b, thereby suppressing cell proliferation after X-ray irradiation.